DO PARENTS INTRODUCE AGRICULTURAL LIVELIHOOD TOWARDS RURAL-YOUTH? Understanding Communication Pattern Between Parents and Rural-Youth related to Agricultural Livelihood in Ciasmara Village, Pamijahan Sub-district, Bogor Regency - Adinugraha, Yogaprasta; Nugroho, David Rizar; Reza, Muhammad; Haikal, Abdurrozieq (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
The regeneration of agricultural workers has decreased in the last 10 years, this is feared to have an impact on food security in Indonesia. There are several things that cause the absence of young workers in agricultural sector, including how agricultural values are passed on to their children. This study will focus on (1) identifying communication frequency between parents and youth in context of agricultural work (2) identifying actors that communicate with rural youth in context of agricultural work. (3) Identifying the discussion topics between parents and rural youth in context of agricultural work. This research was carried out in Ciasmara Village, Bogor Regency from June 2020 - August 2021. Ciasmara Village was chosen as the research location because the village is one of the rice barns in Bogor Regency and the largest rice contributor to the capital city area. A total of 120 village youths were selected as research respondents through purposive sampling method. The results showed that parents still communicated about agriculture to their children in the context of rice cultivation and how to harvest rice. Both of these information are the most frequently discussed information because they are closely related to family labor to save production costs.